2016
DOI: 10.1186/s13000-016-0587-y
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of epithelial-mesenchymal transition markers in the histogenesis of hepatic progenitor cell in HBV-related liver diseases

Abstract: BackgroundThe origin and heterogeneity of hepatic progenitor cells (HPCs) remain unclear. This study aimed to investigate the involvement of epithelial-mesenchymal transition (EMT) in the histogenesis of HPCs.MethodsSurgical liver specimens from patients with HBV-related hepatitis and cirrhosis were investigated with double immunofluorescence labeling to detect antigens associated with HPCs and EMT. Ductular reactions were subjected to quantitative reverse transcription PCR following isolation by laser capture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Interestingly, previous scientific evidences suggested that this natural monomer possesses promising anticancer activities on diverse tumours/cancers (e.g. liver cancer, gastric cancer, breast cancer, lung cancer, pancreatic cancer, colorectal cancer, glioma, bladder cancer and leukaemia) . This paper summarized the previous researches of activities of Paeoniflorin on various cancers in vivo and in vitro, discussed the related molecular mechanisms, and suggested some perspectives of the future investigations, which would be beneficial for the further exploration and development of this natural compound as a clinical cancer drugs.…”
Section: Introductionmentioning
confidence: 93%
“…Interestingly, previous scientific evidences suggested that this natural monomer possesses promising anticancer activities on diverse tumours/cancers (e.g. liver cancer, gastric cancer, breast cancer, lung cancer, pancreatic cancer, colorectal cancer, glioma, bladder cancer and leukaemia) . This paper summarized the previous researches of activities of Paeoniflorin on various cancers in vivo and in vitro, discussed the related molecular mechanisms, and suggested some perspectives of the future investigations, which would be beneficial for the further exploration and development of this natural compound as a clinical cancer drugs.…”
Section: Introductionmentioning
confidence: 93%
“…Beyond this, we also found gene sets, such as E2F and MYC targets, are upregulated in CLD and in HCC in a progressive manner. Indeed, the upregulation of E2F targets has been reported to define a subclass of HCC [74,75]. Thus, tumorigenic transcriptional programmes may already be activated in CLD.…”
Section: Discussionmentioning
confidence: 99%